Aberrant Wnt Signaling in Leukemia - Staal, Frank J. T. (Cancers (Basel), 2016)
The Wnt signaling pathway is essential in the development and homeostasis of blood and immune cells, but its exact role is still controversial and is the subject of intense research. The malignant counterpart of normal hematopoietic cells, leukemic (stem) cells, have hijacked the Wnt pathway for their self-renewal and proliferation. Here we review the multiple ways dysregulated Wnt signaling can contribute to leukemogenesis, both cell autonomously as well as by changes in the microenvironment.